Building Materials And Structural Foundations In The Bujang Valley And Comparisons With Four Regional Settlements - Singh, Meljev Singh Sidhu Sarjit (2018)
This thesis explores building materials and foundations in the Bujang Valley throughout the millennium from 400-1400 CE. The Bujang Valley consists of several loosely related proto-historic settlements that played an important role in international trade. Eight building materials (sandstone, granite, clay, laterite, pebbles, earth, wood and bamboo) are analysed. The aim of this study is to understand the dynamics of the construction industry via the study of the building materials used and the foundations of structures. It also aims to trace the spread of technologies between the Bujang Valley and four coastal settlements of the same period in order to determine whether a homogeneous style of construction existed in the region. The data for this research was collected via field trips and the study of literary sources including old histories of Kedah and archaeology reports. The bulk of the data for this research was taken from literary sources, since most of the sites are no longer extant. All of the permanent building materials were used until the 15th century CE and stopped once the Bujang Valley area ceased to be an international trading hub. Every building material studied was available in Bujang Valley. However, the limited use of sandstone suggests that sandstone items may have been imported even though sandstone was also available locally. There were two types of processing centres, the first of which processed material for structures on site while the second type may have processed material before sending it to the building site. Most of the processing of building material was on a small-scale. Due to differences in the types of structural foundations in the Bujang Valley and in Yarang, Takuapa, Batujaya and Cibuaya, it can be argued that there wasno homogeneity in the architecture of structures from southern Thailand to Java based on foundations of structures, suggesting limited transfer of technologies between the settlements studied.